2009
DOI: 10.1073/pnas.0900355106
|View full text |Cite
|
Sign up to set email alerts
|

Impaired maturation of dendritic spines without disorganization of cortical cell layers in mice lacking NRG1/ErbB signaling in the central nervous system

Abstract: Neuregulin-1 (NRG1) and its ErbB2/B4 receptors are encoded by candidate susceptibility genes for schizophrenia, yet the essential functions of NRG1 signaling in the CNS are still unclear. Using CRE/LOX technology, we have inactivated ErbB2/B4-mediated NRG1 signaling specifically in the CNS. In contrast to expectations, cell layers in the cerebral cortex, hippocampus, and cerebellum develop normally in the mutant mice. Instead, loss of ErbB2/B4 impairs dendritic spine maturation and perturbs interactions of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(192 citation statements)
references
References 32 publications
10
174
3
Order By: Relevance
“…According to previous studies, NRG1 exerts different trophic effects on cortical GABAergic interneurons depending on the length of exposure to the neurotrophic factor Barros et al, 2009;Fisahn et al, 2009;Fazzari et al, 2010). Acute effects include NRG1-triggered GABA release, which involves an increase in membrane excitability in presynaptic terminals Wen et al, 2010).…”
Section: Acute and Subchronic Effects Of Nrg1 On Excitatory Input Synmentioning
confidence: 98%
“…According to previous studies, NRG1 exerts different trophic effects on cortical GABAergic interneurons depending on the length of exposure to the neurotrophic factor Barros et al, 2009;Fisahn et al, 2009;Fazzari et al, 2010). Acute effects include NRG1-triggered GABA release, which involves an increase in membrane excitability in presynaptic terminals Wen et al, 2010).…”
Section: Acute and Subchronic Effects Of Nrg1 On Excitatory Input Synmentioning
confidence: 98%
“…Impaired lateral inhibition in NRG1 Ig-like domain mutant mice could also be improved by clozapine (Rimer et al, 2005). In addition, clozapine could reverse the abnormalities in ErbB4-deficient mice, including decreased anxiety in the open field test, more aggressive activities in the resident-intruder assay and lower PPI level (Barros et al, 2009).…”
Section: Abnormal Behaviours Of Animals With Deficient Nrg1-erbb4 Sigmentioning
confidence: 99%
“…In the last decade, animal studies have shown that animals with abnormal NRG1-ErbB4 functions display schizophrenia-like behavioural abnormalities, including hyperactivities in the novel open-field test and the alternating-Y maze (Barros et al, 2009;Duffy et al, 2008;Gerlai et al, 2000;O'Tuathaigh et al, 2007;Rimer et al, 2005;Stefansson et al, 2002;van den Buuse et al, 2009), deficits in prepulse inhibition (PPI) level (Barros et al, 2009;Dejaegere et al, 2008;Hong et al, 2008;Savonenko et al, 2008;Stefansson et al, 2002;van den Buuse et al, 2009), and lateral inhibition (Rimer et al, 2005), as well as impaired social activities (O'Tuathaigh et al, 2007). These reports provided evidence supporting the potential roles of mutations in NRG1 and ErbB4 genes as risk factors for schizophrenia.…”
Section: Abnormal Behaviours Of Animals With Deficient Nrg1-erbb4 Sigmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, clozapine and haloperidol could improve PPI (prepulse inhibition) deficits in NRG1 and ErbB4 knock-out mice (Barros et al, 2009;Dejaegere et al, 2008;Savonenko et al, 2008); therefore the effects of haloperidol on the expression of NRG1 and ErbB4 observed in this study may provide a mechanism for this behavioural effect.…”
Section: Discussionmentioning
confidence: 60%